Blue Accounting Dan Resolusi Penanganan Limbah Plastik - Syah, Sultan; Syah, Sri Rahayu; Khairin, Fibriyani Nur; Kesuma, Dharma (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
The purpose of this study is to provide an understdan ing of the role of accounting blue in converting plastic waste into environmentally friendly energy to meet human needs. This study used qualitative methods using eco phenomenology. Data is obtained through observation, documentation, and daily activities. This research provides a solution to overcome the problem of plastic waste in the sea. In addition, plastic waste can produce fuel oil with a composition of 10 kg of plastic waste each, producing 6 liters of diesel fuel, 2 liters of gasoline dan 2 liters of fuel providing a solution to the difficulties of fuel experienced by fishermen. The application of this research is beneficial for environmental accounting progress. The novelty/originality of this research was able to overcome the problem of plastic waste to zero. By converting waste into fuel oil, at least three things can be resolved, namely the problem of reducing plastic waste, overcoming the problem of scarcity of fuel oil especially for fishermen, dan generating economic value for the community.